The U.S./Russia/China in new global system of international relations - Sartaj, Reza (International Journal of Business Management and Entrepreneurship, 2022)
In international system, the major appearance of international relations is reflected as the whole interactions among states. The international state system, which in a general sense refers to a set of interrelated units and a pattern of interaction among them, is more demonstrated as structural power to alter the structure of the global political economy. From the definition of Balaam and Veseth (2005), power is the ability of one state (or actor) to get another state (or actor) to do something, even if they don’t want to. Generally, state power can be appeared as capabilities which refer to “Hard Power” and influence as “Soft Power”. The U.S, Russia, and China, as three of five permanent members of the UN Security Council, are currently playing as the major powers in international systems. Those three major power relations are an important component of the international relations and an important factor that impacts the evolution of world configuration and international order. In a sense, to study the international order is to study major power structure. The final disappearance of the world’s two confronting camps by end of the Cold War, and the resulting U.S. sole superpower status, have brought about important changes in the major power relations and international order. After 9/11, the unilateralism and preemptive strategy adopted by the Bush administration strongly affected the major power relations and international order. Therefore, this paper is to examine the basic features and major mechanisms of the present major power relations among those three states, and their interactions to influence the international order.